ROLE OF MEMORY IN SHAPING CHARACTERS IDENTITY IN MAHESH DATTANIS FINAL SOLUTIONS - Suman Sigroha (Soegijapranata Catholic University, 2013)
While writing of contemporary issues Mahesh Dattani constructs a sense of a shared urban cultural identity, which is upper-middle class, professional, English speaking and a cityfied identity. Memory plays a very important part in the plays. Public memory is time and again juxtaposed with personal memory, and it becomes a means to explain and justify the political acts committed for personal interests. This paper looks at how memory, personal as well public, shapes the identities (social, personal and religious) of characters in Mahesh Dattanis Final Solutions. Incidents are important, but only to explain why and how the people populate his plays, acting in ways that they do. The psychological action is of greater relevance than any physical action that takes place in the play. He reveals his characters by placing them in situations where they are forced to analyze themselves in the light of what happened in their lives in the past.